KEPUASAAN PENGGUNA PADA LIMA BESAR PERGURUAN TINGGI SWASTA DI KOTA SEMARANG - Djauhar Edi Purnomo (Neraca, 2010)
User satisfaction is a user’s respon to the disconformity that sensed between previous hopes (or other preformance norm) and actual product performance which tested by the users. This consumen is becoming a key succes factor (KSF) of an organization to keep on survive on it’s field. Population and sample being used in this research are the student of five private university in Semarang. Those university are : UNISSULA, USM, UDINUS, UNIKA, and UNISBANK. The sample that is being use are at the number of 100 respondent devided into 20 respondent in each university. This research users the conjoint analysis, the result shows that in an Academic factor, acreditation sub factor are tend to be liked than curriculum sub factor. In a Non Academic, facilities sub factor are tend to be liked than financing sub factor. Menwhile in Other factors, leadership sub factor are temnd to be liked than location sub factor. The preferences shows by the respondent in this research are also shows that knowledge background and available information influence the satisfaction which become the basis for choosing the university to be a place to study in other to obtain bachlor degree (strata 1). The result of this research can be used by the university to get new student in the next year of study.